Evaluation of hepatic fibrosis – access to non-invasive methods, national practice/guidelines in Central Europe - Jarcuska, Peter; Bruha, Radan; Horvath, Gabor; Simon, Krzysztof; Drazilova, Sylvia (Clinical and Experimental Hepatology, 2016)
Noninvasive methods have improved diagnostic tools of liver fibrosis. Although liver biopsy is the gold standard for diagnosis of hepatis fibrosis, the noninvasive tests are usually much less expensive than liver biopsy, better tolerated, and can be repeated without any risk for the patient. Two groups of these noninvasive tests are included in clinical practice: serum biomarkers and elastography. In our paper we summarize noninvasive diagnostic options for liver fibrosis in the Czech Republic, Hungary, Poland and Slovakia. Noninvasive diagnostic methods, especially elastography, are widely accessible in all countries.